Contact Tracing during an Outbreak of Ebola Virus Disease in the Western Area Districts of Sierra Leone: Lessons for Future Ebola Outbreak Response - Olu, Olushayo Oluseun; Lamunu, Margaret; Nanyunja, Miriam; Dafae, Foday; Samba, Thomas; Sempiira, Noah; Kuti-George, Fredson; Abebe, Fikru Zeleke; Sensasi, Benjamin; Chimbaru, Alexander; Ganda, Louisa; Gausi, Khoti; et al. (Frontiers in Public Health, 2016)
Introduction: Contact tracing is a critical strategy required for timely prevention and control of Ebola virus disease (EVD) outbreaks. Available evidence suggests that poor contact tracing was a driver of the EVD outbreak in West Africa, including Sierra Leone. In this article, we answered the question as to whether EVD contact tracing as practiced in Western Area districts of Sierra Leone from 2014 to 2015 was effective. The goal is to describe contact tracing and identify obstacles to its effective implementation. Methods: Mixed methods comprising secondary data analysis of the EVD case and contact tracing data sets collected from Western Area during the period from 2014 to 2015, key informant interviews of contact tracers and their supervisors and a review of available reports on contact tracing were implemented to obtain data for this study. Results: During the study period, 3,838 confirmed cases and 32,706 contacts were listed in the Viral Hemorrhagic Fever and contact databases for the district (mean 8.5 contacts per case). Only 22.1% (852) of the confirmed cases in the study area were listed as contacts at the onset of their illness which indicates incomplete identification and tracing of contacts. Challenges associated with effective contact tracing included lack of community trust, concealing of exposure information, political interference with recruitment of tracers, inadequate training of contact tracers and incomplete EVD case and contact database. While the tracers noted the usefulness of community quarantine in facilitating their work, they also reported delayed or irregular supply of basic needs such as food and water which created resistance from the communities. Conclusions: Multiple gaps in contact tracing attributed to a variety of factors associated with implementers and communities were identified as obstacles that impeded timely control of the EVD outbreak in the Western Area of Sierra Leone. In future outbreaks, early community engagement and participation in contact tracing, establishment of appropriate mechanisms for selection, adequate training and supervision of qualified contact tracers, establishment of a well-managed and complete contact tracing database, and provision of basic needs to quarantined contacts are recommended as measures to enhance effective contact tracing.